Planning and Integration of ICT on Teacher Education Professional Development for Enhancing Teaching and Learning of Yoruba Migrated Indigenes of Lagos State in Diaspora - Gbesoevi, Emmanuel Semako; Hunpegan, Hendeweh Dorcas; Gbenu, Jide Pius (FKIP-Universitas Riau, 2022)
This study examine planning and integration of ICT on teacher’s professional development among yoruba migrated indigene of Lagos State in Diaspora. This study adopted a descriptive correlational research design. A simple and purposive random sampling techniques was adopted to select the sample for this study. Data was collected through a self-designed questionnaire titled” Planning and Integration of ICT on Teachers Education for Professional Development for Migrated Yoruba Indigenes of Lagos State in Diaspora” (PLICTTEPDMYILSD). The instrument was validated through face and content validity and was found reliable at 0.71 coefficients using a test retest reliability method. Data collected for testing the hypothesis at 0.05 level of significance was analyzed using Pearson’s Product-Moment Correlation Coefficient. The results showed a significant relationship between ICT and teaching and learning outcome of Yoruba Migrated Indigene in Diaspora: a significant relationship between Information communication Technology and teaching effectiveness of Yoruba Migrated Indigenes of Lagos State in Diaspora: a significant relationship between teacher and student accessibility to Information Communication Technology and the productivity the Yoruba Migrated Indigene of Lagos State in Diaspora. It was recommended that proper planning and integration of ICT in education among Yoruba Migrated Indigene of Lagos State in Diaspora.